Queering the museum - Sullivan, Nikki; Middleton, Craig (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Queering the Museum develops a queer analysis of the ways in which museums construct themselves, their core business, and their publics through the, often unconscious, use of inherited ways of knowing and doing. Providing a critique of both the practices and conventions associated with the modern public museum, and the ontological assumptions that inform them, the authors consider recent discourse around inclusion in museums and explore the ways this has been taken up in practice. Highlighting the limits of particular approaches to inclusion, and the failure to move away from a traditional museological paradigm, the book outlines an alternative critical museological approach that the authors refer to as 'queer'. Providing readers with the critical tools necessary for a profound rethinking of museum practice, the book also responds to and problematises the growing call for social inclusion. Queering the Museum will appeal to academics, students and museum and arts sector practitioners with an interest in critical theory or queer practice. It will be of particular interest to those working in the fields of museum studies, sociology, archaeology, anthropology, cultural studies, media, social policy, politics, philosophy and history"--
OCLC-licensed vendor bibliographic record.
Keywords: Museums -- Social aspects; Museums -- Political aspects; Museums -- Educational aspects; Museums and sexual minorities; Sexual minorities; SOCIAL SCIENCE / Gender Studies